Persistent P-Stabilized Boryl Radicals with Bulky Substituents at Boron - Rosenthal, Amos J.; Mallet-Ladeira, Sonia; Bouhadir, Ghenwa; Bourissou, Didier (Synthesis, 2018)
Two new P-stabilized boryl radicals [Ph2P(naph)BAr] (Ar = Tip and Ter) have been prepared and characterized by electron paramagnetic resonance spectroscopy. These radicals are persistent for several days in solution at room temperature. The high steric congestion at boron does not prevent radical reactivity. Two different types of dimerization equilibrium have been observed. The structures of the dimers have been unambiguously established by X-ray diffraction crystallography.
Keywords: radicals; boron; boryl radicals; phosphorus; Gomberg-type dimerization; m-terphenyl; EPR spectroscopy; X-ray diffraction